Neutrophil Homeostasis and Emergency Granulopoiesis: The Example of Systemic Juvenile Idiopathic Arthritis - Malengier-Devlies, Bert; Metzemaekers, Mieke; Wouters, Carine; Proost, Paul; Matthys, Patrick (Frontiers in Immunology, 2021)
Neutrophils are key pathogen exterminators of the innate immune system endowed with oxidative and non-oxidative defense mechanisms. More recently, a more complex role for neutrophils as decision shaping cells that instruct other leukocytes to fine-tune innate and adaptive immune responses has come into view. Under homeostatic conditions, neutrophils are short-lived cells that are continuously released from the bone marrow. Their development starts with undifferentiated hematopoietic stem cells that pass through different immature subtypes to eventually become fully equipped, mature neutrophils capable of launching fast and robust immune responses. During severe (systemic) inflammation, there is an increased need for neutrophils. The hematopoietic system rapidly adapts to this increased demand by switching from steady-state blood cell production to emergency granulopoiesis. During emergency granulopoiesis, the de novo production of neutrophils by the bone marrow and at extramedullary sites is augmented, while additional mature neutrophils are rapidly released from the marginated pools. Although neutrophils are indispensable for host protection against microorganisms, excessive activation causes tissue damage in neutrophil-rich diseases. Therefore, tight regulation of neutrophil homeostasis is imperative. In this review, we discuss the kinetics of neutrophil ontogenesis in homeostatic conditions and during emergency myelopoiesis and provide an overview of the different molecular players involved in this regulation. We substantiate this review with the example of an autoinflammatory disease, i.e. systemic juvenile idiopathic arthritis.